Avaliação de políticas públicas : ensaios em economia da saúde e da educação - Frio, Gustavo Saraiva (2020)
Public policies grow in Brazil due to Brazilians’ needs for better living conditions or as a way of dealing with fiscal issues. The implementation of such policies may not have the effects which were desired previously, generating negative externalities to the population or innocuous results. Otherwise, it is possible for results to be as expected at implementation time. Hence this thesis has the objective of using the public policy evaluation econometrics toolkit to asses the effects of three programs regarding either health or education of children and young people or adults and elders. The major findings show that the HPV vaccination campaign – effective in preventing the disease, which is the main cause of cervical cancer – doesn’t have externalities in the behavior of vaccinated girls, the public policies for stimulating physical activity have positive effects on older adults – decrease in blood pressure, increase in self-reported health, decrease in symptoms of depression-, specially men, and the policy of delayed wages lowers standardized grades in Math and Portuguese in the state education system in Minas Gerais and Rio Grande do Sul, affecting middle school graduates. It can be concluded that it is necessary to make public policy evaluation so that the expenditure of both federal and state government is efficient and may improve the population’s general well-being, such knowledge is also important to mark improvements in public policies.